1979
DOI: 10.1128/aem.38.6.1069-1073.1979
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Existence of “Survival Factors” as an Explanation for Some Peculiarities of Yeast Growth, Especially in Grape Must of High Sugar Concentration

Abstract: The retardation and arrest of fermentation, observed before the complete sugar consumption of high-sugar grape must, come from an inhibition of the yeast metabolism during its decline phase and are variable with the strain. The addition of nutritional growth factors stimulates the initial growth of the yeast but is ineffective in the decline phase. Some substances, known previously as yeast anaerobic growth factors (sterols, oleanolic acid, oxytocin), in some conditions (initially aerated grape must and aerobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

1989
1989
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 4 publications
1
16
0
2
Order By: Relevance
“…In wine microbiology, it has already been reported that several parameters influence the successful completion of the fermentation and the production of desirable flavour compounds. In particular, several studies focused on the impact of the grape juice constituents, such as sugars (Erasmus et al , Ferreira et al ), nitrogenous compounds (Bely et al , Blateyron and Sablayrolles , Jiménez‐Martí et al , Mouret et al ), lipids (Lafon‐Lafourcade et al , Luparia et al , Rollero et al , Casalta et al ), oxygen (Sablayrolles et al , Julien et al , Coetzee et al ), vitamins (Bataillon et al , Thomas and Surdin‐Kerjan , Wang et al , Bohlscheid et al ) and minerals (Pereira , Birch et al , Ibanez et al ). The redox metabolism of the yeast can also play a substantial role in the synthesis of aroma compounds, because their synthesis involves a wide range of dehydrogenases, thus impacted by the balance of NAD(P) + /NAD(P)H (oxidized Nicotinamide Adenine Dinucleotide (Phosphate) oxidized / reduced Nicotinamide Adenine Dinucleotide (Phosphate)) (Fariña et al , Bloem et al ).…”
Section: Introductionmentioning
confidence: 99%
“…In wine microbiology, it has already been reported that several parameters influence the successful completion of the fermentation and the production of desirable flavour compounds. In particular, several studies focused on the impact of the grape juice constituents, such as sugars (Erasmus et al , Ferreira et al ), nitrogenous compounds (Bely et al , Blateyron and Sablayrolles , Jiménez‐Martí et al , Mouret et al ), lipids (Lafon‐Lafourcade et al , Luparia et al , Rollero et al , Casalta et al ), oxygen (Sablayrolles et al , Julien et al , Coetzee et al ), vitamins (Bataillon et al , Thomas and Surdin‐Kerjan , Wang et al , Bohlscheid et al ) and minerals (Pereira , Birch et al , Ibanez et al ). The redox metabolism of the yeast can also play a substantial role in the synthesis of aroma compounds, because their synthesis involves a wide range of dehydrogenases, thus impacted by the balance of NAD(P) + /NAD(P)H (oxidized Nicotinamide Adenine Dinucleotide (Phosphate) oxidized / reduced Nicotinamide Adenine Dinucleotide (Phosphate)) (Fariña et al , Bloem et al ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, most of the identified species in 2005, are known to be well adapted to environmental stress such as sugars and ethanol concentration, low pH and low temperature (FREDLUND et al, 2002). Then, the more the composition of grape must such as sugar concentrations (LAFON-LAFOURCADE et al, 1979), phenolics compounds content and the pH (LAFON-LAFOURCADE and RIBÉREAU-GAYON 1983) is atypical, the more these indigenous species should be favoured. The increase of SO2 added after crushing cannot be considered as an alternative for reducing the indigenous population.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in low solids ferments, depending on other factors such as phytolipid concentration and the dissolved oxygen concentration at inoculation or later during fermentation, yeast growth may be limited by lipid and sterol availability, compromising the total amount of biomass that is able to form (Andreasen and Stier , Lafon‐Lafourcade et al. , Ingledew and Kunkee , Houtman and du Plessis ). As discussed previously, the sterol content of ADY can vary between batches and between strains.…”
Section: Yeast Rehydration and The Use Of Rehydration Additivesmentioning
confidence: 99%
“…Exogenous addition of ergosterol has been shown to facilitate fermentation in anaerobic, highly clarified conditions (Lafon‐Lafourcade et al. , Houtman and du Plessis , Ingledew and Kunkee ) and ergosterol‐enriched yeast show enhanced growth during anaerobiosis (Deytieux et al. ).…”
Section: Fermentation Additives: How and Under What Circumstances Domentioning
confidence: 99%